Edukasi Warga SD Negeri Curug Manis dalam Rangka Cegah Diare pada Anak dengan Hidup Sehat - Ani Fuziyanti; Herlina Julianna; Poppy Maratu Sholihah; Tiara Putriana; Sinta Aprilia; Mila Ermila Hendriyani (Poltekita: Jurnal Pengabdian Masyarakat, 2022)
Diarrhea is a condition characterized by an increase in the frequency and a decrease in the consistency of bowel movements. Diarrhea is often experienced by school children caused by the behavior of children who do not understand about clean and healthy living. Incidents can happen to anyone who does not pay attention to personal hygiene. It is hoped that there will be a change in the behavior of clean and healthy living for school residents and the unhealthy school environment community in order to become healthy. This service aims to determine and analyze the determinants of diarrheal disease in children at SDN Curug Manis. This service was carried out at SDN Curug Manis using survey methods and interviews with residents of SDN Curug Manis with a total of 58 participants. The results of this service showed that participants were very enthusiastic in all stages of this activity, starting from the interview stage (pre-test) which showed that participants did not fully know about the prevention of diarrhea. One proof of the success of this activity is seen from the post-test results, on average students answered questions related to diarrhea prevention correctly. This shows that there is an increase in knowledge for students about diarrhea compared to when it has not been explained about diarrhea in children.   ABSTRAK Diare merupakan suatu kondisi yang ditandai dengan peningkatan frekuensi dan penurunan konsistensi buang air besar. Diare sering dialami oleh anak sekolah yang disebabkan oleh perilaku anak yang kurang paham mengenai hidup bersih dan sehat. Kejadian dapat terjadi pada siapa saja yang tidak memperhatikan kebersihan diri. Diharapkan adanya perubahan perilaku hidup bersih dan sehat warga sekolah dan masyarakat lingkungan sekolah yang tidak sehat agar menjadi sehat. Pengabdian ini bertujuan untuk mengetahui dan menganalisis determinan penyakit diare pada anak di SDN Curug Manis. Pengabdian ini dilaksanakan di SDN Curug Manis menggunakan metode survei dan wawancara pada para warga SDN Curug Manis dengan total peserta 58. Hasil dari pengabdian ini menunjukkan bahwa peserta sangat antusias pada semua tahapan kegiatan ini, mulai dari tahap wawancara (pre-test) yang menunjukkan bahwa peserta belum sepenuhnya mengetahui tentang pencegahan diare. Salah satu bukti keberhasilan kegiatan ini adalah dilihat dari hasil post-test, rata-rata siswa menjawab pertanyaan terkait pencegahan diare dengan benar. Hal itu menunjukkan bahwa adanya peningkatan pengetahuan bagi siswa tentang diare dibandingkan saat belum dijelaskan tentang diare pada anak.